KONTRIBUSI APLIKASI SISTEM INFORMASI GEOGRAFIS (SIG) DALAM BERBAGAI SKALA KAJIAN ARKEOLOGI LANSEKAP - Yuwono, J. Susetyo Edy (BRIN, 2007)
The recent development of the Geographical Information System (GIS) has had an impact on archaeological interests, both at the level of estimation and site exploration, presentation of site distribution, various types of spatial analysis and modeling, to the level of archaeological resource management especially for decision making. On the side of archaeological studies, the demands and tough task ahead, is how this discipline is able to access, process and structurize, present, and update all geo-cultural information in the dimensions of form, time and space which are increasingly unlimited in complexity. All forms of geo-cultural information and their dynamics, which are the substance of a landscape condition, require archaeology to